2021
DOI: 10.3390/molecules26154504
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Secondary Metabolites Compounds Isolated from Phylum Actinobacteria and Its Therapeutic Applications

Abstract: The current review aims to summarise the biodiversity and biosynthesis of novel secondary metabolites compounds, of the phylum Actinobacteria and the diverse range of secondary metabolites produced that vary depending on its ecological environments they inhabit. Actinobacteria creates a wide range of bioactive substances that can be of great value to public health and the pharmaceutical industry. The literature analysis process for this review was conducted using the VOSviewer software tool to visualise the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 109 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…The relative abundance of Proteobacteria in the LLL10 and GLL10 groups was significantly lower ( P < 0.05) than that in the HLL10 group. Actinobacteria produced various secondary metabolites with different physiological and metabolite activities and had the potential to produce new bioactive compounds and enzymes, including aminoglycosides, glycopeptides, and degrading enzymes . The relative abundance of Actinobacteria was significantly higher in the LLL36 group ( P < 0.05) than that in the LLL10 group.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The relative abundance of Proteobacteria in the LLL10 and GLL10 groups was significantly lower ( P < 0.05) than that in the HLL10 group. Actinobacteria produced various secondary metabolites with different physiological and metabolite activities and had the potential to produce new bioactive compounds and enzymes, including aminoglycosides, glycopeptides, and degrading enzymes . The relative abundance of Actinobacteria was significantly higher in the LLL36 group ( P < 0.05) than that in the LLL10 group.…”
Section: Resultssupporting
confidence: 88%
“…Actinobacteria produced various secondary metabolites with different physiological and metabolite activities and had the potential to produce new bioactive compounds and enzymes, including aminoglycosides, glycopeptides, and degrading enzymes. 30 The relative abundance of Actinobacteria was significantly higher in the LLL36 group (P < 0.05) than that in the LLL10 group. This result showed that LRS might be degraded more completely at 36 h. At the family level, after LLL, GLL, and HLL treatment, the main microbiota included Lactobacillaceae, Enterobacteriaceae, Bifidobacteriaceae, and Peptostreptococcaceae (Figure 3C).…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Streptomyces are Gram-positive, filamentous, spore-forming bacteria that have a relatively large genomic (DNA) sequence with a high guanine and cytosine (G + C) content 1 , 10 . Streptomyces comprise a very important bacterial genus that contains over 800 species 11 which are recognized worldwide as an inexhaustible source of antibiotics used in human therapy 3 , 12 , 13 . Antibiotics derived from the Streptomyces genus play a crucial role in the medical sector.…”
Section: Introductionmentioning
confidence: 99%
“…Typical BGCs contain “core” genes responsible for the biosynthesis of a molecular scaffold, accessory genes encoding enzymes for scaffold modification, genes that regulate the BGC’s expression, and resistance genes for self-protection against the endogenously produced compound ( 1 ). Actinomycetes, filamentous Gram-positive bacteria of the phylum Actinobacteria , produce thousands of SMs, including ca 50% of all clinically used antibiotics ( 2 ). Actinomycetes protect themselves from the toxic effects of endogenously produced antibiotics using a variety of specific mechanisms ( 3 ).…”
Section: Introductionmentioning
confidence: 99%